1995
DOI: 10.1093/genetics/141.4.1563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of 36 mutations at the mouse pink-eyed dilution (p) locus.

Abstract: Thirty-six radiation- or chemically induced homozygous-lethal mutations at the p locus in mouse chromosome 7 have been analyzed at 17 loci defined by molecular probes to determine the types of lesions, numbers of p-region markers deleted or rearranged, regions of overlap of deletion mutations, and genetic distances between loci. A linear deletion map of the [Myod1, Ldh3]-[Snrpn, Znf127] region has been constructed from the molecular analyses of the p-locus deletions. The utility of these deletions as tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…For 35 of the mutations listed in Table 1, kidney and liver homogenates of heterozygotes were tested for LDH (lactate dehydrogenase) activity; only one mutation, p461"20n, exhibited reduced activity (MENDEL 1987). Similar results were obtained for 30 plethal mutations tested with a probe for Ldhl; again p46nF'" was the only mutation in which this locus was found to be deleted (JOHNSON 1990;JOHNSON et al 1995). Analyses of offspring of a cross to M. spretus indicated that the serum amyloid A (Sua) gene complex is also missing in p46DF'"f' (MENDEL 1987;JOHNSON et al 1995), whereas sequences corre-tations, p46lWiOLl…”
Section: Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…For 35 of the mutations listed in Table 1, kidney and liver homogenates of heterozygotes were tested for LDH (lactate dehydrogenase) activity; only one mutation, p461"20n, exhibited reduced activity (MENDEL 1987). Similar results were obtained for 30 plethal mutations tested with a probe for Ldhl; again p46nF'" was the only mutation in which this locus was found to be deleted (JOHNSON 1990;JOHNSON et al 1995). Analyses of offspring of a cross to M. spretus indicated that the serum amyloid A (Sua) gene complex is also missing in p46DF'"f' (MENDEL 1987;JOHNSON et al 1995), whereas sequences corre-tations, p46lWiOLl…”
Section: Methodssupporting
confidence: 55%
“…Similar results were obtained for 30 plethal mutations tested with a probe for Ldhl; again p46nF'" was the only mutation in which this locus was found to be deleted (JOHNSON 1990;JOHNSON et al 1995). Analyses of offspring of a cross to M. spretus indicated that the serum amyloid A (Sua) gene complex is also missing in p46DF'"f' (MENDEL 1987;JOHNSON et al 1995), whereas sequences corre-tations, p46lWiOLl…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…1), large enough to include several undiscovered genes. Arguing against this explanation, however, several large deletions that include the p gene do not result in hypopigmentation in heterozygous mice [Johnson et al, 1995]; thus, a putative unknown pigmentation gene would have to have been introduced into this region in the human lineage subsequent to the mammalian radiation. Third, and we believe most likely, hypopigmentation in PWS and AS may result from reduced expression of the intact P allele in the specific context of large proximal 15q deletions.…”
Section: Discussionmentioning
confidence: 99%